Antimicrobial therapy for acute cholangitis and cholecystitis - Kujiraoka, Manabu; Asai, Koji; Moriyama, Hodaka; Saida, Yoshihisa; Watanabe, Ryutaro; Watanabe, Manabu; Matsukiyo, Hiroshi (Tando, 2021)
Acute cholangitis and cholecystitis are diseases importantly requiring to decide a treatment policy with careful consideration of the time from onset to diagnosis before the pathological conditions become severe. The principles of treatment are local control of infection focus by cholecystectomy or biliary drainage and antimicrobial therapy. Antimicrobial therapy has also been changing due to the spread of multiple drug-resistant Gram-negative bacteria. According to Tokyo Guidelines 2018 (TG18), it proposes recommended medication for initial treatment on the basis of the classification as community-acquired infection (by severity) or healthcare associated infection while selecting antibacterial drug in consideration of susceptibility pattern (antibiogram) at each institution. In addition, it is important to de-escalate the empirically-administered initial drug to an optimal drug when proving susceptivity results with the identification of microorganism in blood culture/bile culture test. In this article, we describe antimicrobial therapy for acute cholangitis and cholecystitis on the basis of TG18.